ChemInform Abstract: Ditechnetium Heptoxide Revisited: Solid‐State, Gas‐Phase, and Theoretical Studies. Issue 51 (5th December 2016) - Poineau, Frederic; et al.,
Abstract: In view of the vitrification of high‐level nuclear waste, Tc2 O7, known as a volatile compound during vitrification, is prepared by thermal oxidation of TcO2 under O2 (Pyrex tube, 450→25 °C, 3 h).